Applicant versus employee scores on self-report emotional intelligence measures - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2011)
There exists growing interest to assess applicants' emotional intelligence (EI) via self-report trait-based measures of EI as part of the selection process. However, some studies that experimentally manipulated applicant conditions have cautioned that in these conditions use of self-report measures for assessing EI might lead to considerably higher scores than current norm scores suggest. So far, no studies have scrutinized self-reported EI scores among a sample of actual job applicants. Therefore, this study compares the scores of actual applicants at a large ICT organization (n = 109) on a well-known self-report measure of EI to the scores of employees already working in the organization (n = 239). The current study is the first to show that applicants' scores on a self-report measure of EI during the selection process are indeed higher (d = 1.12) and have less variance (SD ratio = 0.86/1) than incumbents' scores. Finally, a meta-analytic combination of our results with those of earlier research showed that a score increase of about 1 SD in applicant conditions seems to be the rule, regardless of the type of setting, self-report EI measure, and within-versus between-subjects design employed.